Multi-omics analysis elucidates phased defense and resource allocation trade-offs in fusarium resistance of maize - Aiguo Su; Senlin Xiao; Zhiyong Li; Sairu Duan; Shuaishuai Wang; Haixia Zhang; Ruyang Zhang; Jinfeng Xing; Chunhui Li; Xiaqing Wang; Yanxin Zhao; Shuai Wang; et al. (Plant Stress)
Fusarium graminearum-induced ear rot may lead to severe yield losses and mycotoxin contamination, which threaten global maize production. To dissect resistance mechanisms, we integrated a genome-wide association study (GWAS) of 420 maize inbred lines across five environments with a time-resolved transcriptomics analysis of resistant and susceptible genotypes. On the basis of GWAS, 151 significant single nucleotide polymorphisms (SNP) were identified, including novel loci in bin 7.04 and known resistance hotspots in bin 3.04. By comparing the transcriptomes of resistant (X178) and susceptible (B73) lines during early infection phases, we detected 1537 differentially expressed genes associated with pathways related to plant immune responses (e.g., defense signaling, secondary metabolism, redox homeostasis, and cytoskeletal reorganization). Additionally, 32 potential resistance genes were differentially expressed according to our transcriptome analysis, which enabled the prioritization of candidate genes, including ZmTRX (thioredoxin), ZmGuLO (ascorbate biosynthesis), and ZmVOZ1 (transcription factor). We propose that resistant maize lines have phased defense responses that transiently suppress the synthesis of storage-related proteins (e.g., α-zein), reallocate resources for immunity-related activities, and balance stress response-associated trade-offs via dynamic regulation.